The impact of internal marketing practices on the job satisfaction and performance of the employees of the Sudanese French Bank - Babaker, Omar Ali (Journal of Economic, Administrative and Legal Sciences, 2018)
Internal marketing is one of the modern concepts that relate directly to the human element. It is one of the concepts that provide an appropriate working environment to help employees achieve better marketing performance. The relative importance of internal marketing in the organization varies according to the roles of the employees and their relationship with the customers. The more the work environment is characterized by the acceptance and satisfaction of the employees (internal marketing) the greater the job satisfaction of the employees and thus the better performance.The problem of the study was the following question: What is the impact of internal marketing practices on the job satisfaction and performance of the employees of the Sudanese French Bank? The main objective of the study is to investigate the impact of internal marketing practices on the job satisfaction and performance of employees Sudanese French. The main hypothesis is whether there is a statistically significant effect of the internal marketing practices on the job satisfaction of the employees of the Sudanese French Bank and on the performance of the workers of Sudanese French Bank. To evaluate the hypothesis of the study a number of statistical methods have been used. The results of the study indicate that internal marketing through its studied dimensions plays an important role because of its positive impact on the job satisfaction of the employees of the Sudanese French Bank. It also has a positive impact on their performance of their work with high quality, showing that achieving high levels of job satisfaction for employees of the Sudanese French Bank and it has a positive impact on the performance of their work with high quality. These factors provide an appropriate working environment based on equality within the Bank's regulations and instructions, and make it a culture for its employees, providing effective communication methods for establishing positive relationships in the work environment, And the provision of training programs to provide employees with the skills that enable them to accomplish the tasks entrusted to them efficiently all together will work to achieve high levels of job satisfaction that contribute to the performance of their work with high quality and quickly and at the cost of Less.
Keywords: Sudanese French Bank; job satisfaction; employee performance; internal marketing